(untitled) (Research, Society and Development, 2022)
This article aims to problematize the role of the Cultural Industry in the constitution of childhoods for consumption. This is a theoretical essay based on studies by Adorno and Horkheimer (1985), Dornelles (2005; 2012); Henriques (2012), Schor (2009) and Oliveira (2011) among others. These theorists helped us to understand the shaping role of the Cultural Industry in children’s ways of being, acting and thinking, leading children to consume more and more. In contemporary times, digital media have been widely used by children and childhood has been reconfigured, lived in a confined way and with a blunted conscience and focused on consumption. At the heart of processes of enchantment and empowerment of children, the cultural industry, with a view to consumption, through techniques of convincing that products and goods and services are necessary for their survival. Thus, capitalist society is governed by the market and profit and has, in child subjects, potential individuals to develop the culture of consumption.